Determinación de la factibilidad ambiental del coprocesamiento de llantas en hornos cementeros de vía seca mediante el análisis de impactos ambientales utilizando el software SIMAPRO 7.3.3 - Víquez-Zamora, María Daisy (Instituto Tecnológico de Costa Rica, 2014)
Co-processing alternative fuels in cement kilns has been an alternative found by the cement industry to offset the great amounts of atmospheric emissions for which they are responsible. This project aimed to identify the environmental impacts of the emissions from the traditional petroleum coke process with an alternative process, partially replacing of petroleum coke for end-of-life tires where a substitution rate of 25% was considered to compare the environmental impacts of both processes. A detailed emissions data from an study made by Conesa, et al. at a cement plant in Alicante, Spain and Ecoinvent data base was used. The environmental impacts were evaluated using the methodology CML 2 baseline 2000 V2.05 available in SimaPro 7 software. The results indicated a decrease on the environmental impacts for the co-processing, related to the reduction of emissions of CO2, SO2 and other substances that affect the human health and the environment. The results confirm the environmental feasibility of coprocessing end of life tires in cement kilns.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2014.
Keywords: Emisiones de humo; Combustibles; Producción de cemento; Impacto ambiental; Hornos; Petróleo; Salud